Estimating Deterioration Rate of Some Carbonate Rocks Used as Building Materials under Repeated Frost Damage Process, China - Marzouk Mohamed Aly Abdelhamid; Dong Li; Gaofeng Ren; Congrui Zhang (Advances in Materials Science and Engineering)
The degradation of natural rocks due to severe environmental conditions can influence their durability over an extended period of time. This research aims to investigate the long-term durability or disintegration rate of rocks used as construction materials under severe climatic conditions using frost damage action, and the deterioration rate was assessed using mathematical decay function approach. The mathematical model assumes an initial order operation and gives purposeful properties for the deterioration rate of rocks due to frost action. For this reason, six different limestone types used as building materials were quarried from limestone mine in China and subjected to a series of laboratory tests to determine the mineralogical, petrographical, physical, and mechanical characteristics. Then, 50 cycles of frost damage process was performed, and after each 10 cycles, the unconfined compressive strength, point load strength, and Schmidt rebound were determined. The disintegration rate or integrity loss characteristics of each rock type were assessed using the mathematical decay function approach parameters. This approach proved that the disintegration rate varies for the rocks of the same type especially which were extracted from the same areas, the rock durability under frost damage conditions can be estimated with good accuracy, the parameters of this model saved a lot of time and provided important practical features to assess a rapid durability, and hence, there is no need to carry out the frost damage test which is slow and consumes time.